Correlation of Peak Systolic Velocity Value with Wagner Score in Diabetic Foot Ulcer patients in RSUP Dr. M. Djamil Padang - Fernando Laroza; Raflis Rustam; Vendry Rivaldy (HM Publisher, 2021)
Background: Diabetic foot ulcers are one of the chronic complications of diabetes mellitus (DM) in the form of wounds on the skin surface of the feet of DM patients accompanied by internal tissue damage or tissue death, either with or without infection, which is associated with the presence of neuropathy and or peripheral arterial disease in patients with DM. The World Health Organization (WHO) states that at least 422 million people suffer from DM A new alternative parameter for assessing the degree of peripheral ischemia is ankle peak systolic velocity (PSV). The rationale for PSV is based on the observation that in the ischemic limb, blood travels at a much slower rate in the distal leg arteries than in the nonischemic limb. PSV is a quick and easy test to assess the patient's vascular status and monitor the development of diabetic foot ulcers, and can assess the degree of ischemia and predict healing of diabetic foot ulcers. This study aims to determine the Correlation of Peak Systolic Velocity Value with Wagner Score in Diabetic Foot Ulcer patients in RSUP Dr. M. Djamil Padang. Methods: This research is analytic observational with cross sectional design, the research uses primary data. This research will be conducted at the RSUP Dr. M. Djamil Padang from July 2021 to October 2021. The population in this study were diabetic foot ulcer patients who came for treatment at Dr. M. Djamil Padang. A sample of 32 patients Diabetic foot ulcer met the inclusion criteria. Univariate analysis was conducted to describe each of the variables studied. Numerical data is normally distributed, then it is presented in the form of mean ± standard deviation (SD), whereas if the numerical data is not normally distributed then it is presented in the form of median, minimum and maximum. Categorical data is presented in the form of frequency and percentage of each category. Bivariate analysis was started by using the data normality test using the Shapiro Wilk test (n<50). In testing the correlation between Peak Systolic Velocity and Wagner Score in diabetic foot ulcer patients, the Pearson correlation test is used if the data is normally distributed. Data analysis using SPSS version 22.0. Results: more than half of the subjects (65.6%) are male. The mean age of the subjects was 60.46±10.06 years. More than half of the subjects (62.5%) had a normal body mass index. The average length of suffering from diabetes mellitus was 5.48 ± 2.26 years. Half had a history of smoking (59.4%), a small proportion of subjects had hypertension (21.9%), hypercholesterolemia (6.3%) and neuropathy (12.5%). More than half of the subjects (53.1%) had immunopathies. There is a correlation between the popliteal PSV value and the Wagner score in diabetic ulcer patients (p<0.05), with a moderate correlation strength (r=-0.463) and a negative direction. There is a correlation between the PSV dorsali pedis value and the Wagner score in diabetic ulcer patients (p<0.05), with a strong correlation strength (r=-0.720) and in a negative direction. Furthermore, there is a correlation between the posterior tibial PSV value and the Wagner score in diabetic ulcer patients (p<0.05), with a moderate correlation strength (r=-0.530) and a negative direction. Conclusion: There is a correlation between the popliteal, tibialis posterior, dorsalis pedis PSV value and the Wagner score in diabetic foot ulcer patient